Experiments of a new generation points strategy in a multilocal method - Baniya, Amulya (2020)
Nonlinear programming problems appear frequently in industrial/real problems. It is important to obtain its solution in the lowest time possible, since the company could benefit from this. Taking this into account, a derivative free method (MCSFilter method) is addressed with a different strategy to generate the initial points to start each local search. The idea is to spread more the points so that the code execution will require a shortest amount of time when compared with the MCSFilter method execution. Some experiments were performed with simple bounds problems, equality and inequality constraint problems, chosen from a set of well known nonlinear problems. The results obtained were encouraging and with the new strategy the method needs less time to obtain the global solution.